Les STS ont-elles un Sud ? - David Dumoulin Kervran; Mina Kleiche-Dray; Mathieu Quet (Revue d'anthropologie des connaissances)
Social studies of science (STS, science studies) have played an important role in the renewal of social sciences in the course of their institutionalisation. However, especially in France, they have paid only limited attention to the research on science done in the South. The diverse perspectives developed from/on the South would, if taken into account, broaden the discussion upon knowledge, its places and circulation. In particular, we think that postcolonial approaches provide relevant tools for this reflection and that they give the means for a more mature globalization of STS - relying on a better integration of the Global South to the science studies landscape. Our proposal is developed as such: 1) understanding why science studies have shown little interest for the South until recently, 2) analysing the processes which have enabled the move of STS to the South, 3) mapping the challenges of the “creolization” of STS that mixes post-colonial approaches with science studies approaches.